The Effects of Different Irrigation Scheduling Approaches on Seed Yield and Water Use Efficiencies of Cotton - Safiye Pınar Tunalı; Talih Gürbüz; Necdet Dağdelen; Selin Muradiye Akçay (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted in the Aegean region conditions of Turkey in 2020. It was carried out on May-505, a local cotton variety. The study examined the variation of seed yield, water use efficiency (WUE), and irrigation water use efficiency (IWUE) of cotton with different irrigation programs and water levels. The field trial, which was designed as two factors and three replications, was designed according to the randomized complete block trial design. Four different irrigation levels (IL) (100%, 67%, 33%, and 0%) and two different irrigation scheduling approaches (gravimetric and pan evaporation) were investigated in the study. Seasonal water use values in treatments varied between 215 (0%) and 746 (100% - Pan evaporation approach) mm during the production period. The average yield values obtained with irrigation levels, which have essential effects on cotton seed yield, are listed as follows; 2057 kg ha-1 (IL-0%), 3471 kg ha-1 (IL-33%), 3771 kg ha-1 (IL-67%), and 5083 kg ha-1 (IL-100%). It was determined pan evaporation applications performed higher yields than gravimetric applications. WUE values were between 0.63 – 1.04 kg m-3. The gravimetric method’s yield response factor (ky) was 0.73, and the pan evaporation method’s yield response factor (ky) was 0.89. These results show that cotton is tolerant of water stress. In conclusion, although the pan evaporation approach with 100% treatment is suggested for cotton production in the parts of the Aegean region within the semi-arid climate zone, while water resources are sufficient. When the results are evaluated in terms of seed cotton yield for a deficit irrigation strategy, IL-67% treatment with a gravimetric approach can be used.